The Study of the Qing Dynasty Yanyanyue - YI ZHANG, EMILY (Transactions on Social Science, Education and Humanities Research, 2024)
During the Qing dynasty, Yanyan Yue served as a backdrop to court ceremonies and a dynamic platform for cultural diplomacy. Innovations in banquet music during this period reflected a blend of Han Chinese and Manchu traditions, allowing the Qing court to celebrate its grandeur and sovereignty through these musical expressions. This paper summarizes the evolution of Yanyan Yue, especially the development of Yanyan Yue in the Qing Dynasty, and combs the composition of the musical instruments of Yanyan Yanyan Yue. The purpose is to illustrate the national development and integration in the Qing Dynasty through the changes in musical instruments.